Fractures in Children before 1-Year: Place Abuse - Caryne Mboutol-Mandavo, Dr (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To study the epidemiological and diagnostic aspects of fractures in children before the age of 1 year and identify the place of abuse. Materiel and methods: we conducted a retrospective study in the Pediatric Surgery over a period of 2-year. We got 40 cases of fractures occurred before the age of 1 year. Results and Discussion: The main causes are the fall with 45% of cases, followed by the receipt of a load with 20% of cases, and traditional massage with 12.5% of cases. The main locations of these fractures are the femur (31.1%), humerus (20%) and the clavicle (17.8%). In applying the criteria Bayreuther, a likely accidental is retained in 67.5% of cases and abuse is suspected in 25% of cases, 7.5% of cases were not classified due to lack of clinical data and/or radiological fracture for linking to an accident or abuse. Fractures of the child before the 1st year of life are, in general, due to domestic accidents. However, a number of them may be due to intentional injuries or non-accidental injury. Conclusion: Abuse is a possible cause of fractures in children under 1-year should be systematically sought to the recurrences.